2023
DOI: 10.1101/2023.02.08.527612
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Sex-specific declines in cholinergic-targeting tRNA fragments in the nucleus accumbens in Alzheimer’s disease

Abstract: Females with Alzheimer's disease (AD) present accelerated damage to cholinergic neurons and undergo accelerated cognitive decline compared to males, but the underlying mechanisms are incompletely understood. Here, we report that tRNA fragments (tRFs) carrying complementary sequences to cholinergic transcripts (CholinotRFs) may causally contribute to both these phenomena. We found that the nucleus accumbens of female brains, a brain region enriched in cholinergic neurons, exhibits larger CholinotRF decreases co… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 119 publications
1
17
0
Order By: Relevance
“…Unlike the ‘ changing of the guards’ exchange of Cholinergic-targeting miRs to tRFs in blood cells from ischemic stroke patients [31], or the sex- and disease-related loss of tRFs in the brain of women living with Alzheimer’s disease [32], we observed hepatic ‘in tandem’ decline of LysTTT-5’tRFs and miR-194-5p, which may jointly contribute to the steatosis process through complementary impacts on distinct pathways. Supporting human relevance, miR-194-5p decline also occurred in human-originated Hep G2 cells following a short 48h exposure to OA (∼10%), with further reduction after 72h and one week exposure to OA (∼20%).…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…Unlike the ‘ changing of the guards’ exchange of Cholinergic-targeting miRs to tRFs in blood cells from ischemic stroke patients [31], or the sex- and disease-related loss of tRFs in the brain of women living with Alzheimer’s disease [32], we observed hepatic ‘in tandem’ decline of LysTTT-5’tRFs and miR-194-5p, which may jointly contribute to the steatosis process through complementary impacts on distinct pathways. Supporting human relevance, miR-194-5p decline also occurred in human-originated Hep G2 cells following a short 48h exposure to OA (∼10%), with further reduction after 72h and one week exposure to OA (∼20%).…”
Section: Discussionmentioning
confidence: 64%
“…The initial elevation in LysTTT-5’tRF following short exposure to OA is potentially an attempt of the cells to cope with the cellular stress due to the lipid overload exposure, which may lead to enhanced tRNA cleavage and LysTTT-5’tRF production. However, after long exposure to OA, the hepatocytes tRNA reservoir may be depleted, ultimately resulting in decreased levels of LysTTT-5’tRFs and weaker protection from LDs accumulation, and in essence mimicking the female-specific depletion of mitochondrial-originated tRFs from nucleus accumbens [32].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…tRFs that modulate cholin-ergic transcripts in the nucleus accumbens may potentially lead to accelerated cognitive decline in females with AD. 57 Furthermore, sex hormones influence numerous neural/behavioral functions. Basal forebrain cholinergic neurons express estrogen receptors, 58 and estradiol regulates cholinergic neurotransmission by increasing choline acetyltransferase levels in the basal forebrain and hippocampal ACh release.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have focused on the pathogenic role of calcium dysregulation caused by RyR channel leakage in AD 59–63 . An intriguing recent study revealed the contribution of cholinergic targeting tRFs in the nucleus accumbens to the phenomenon of accelerated dementia and cholinergic neuron loss in female AD patients, suggesting the potential of sex‐adjusted anticholinesterase therapy in the treatment of AD 64 . As mentioned above, chemical modifications regulate the production of tsRNAs and are involved in the stress response.…”
Section: Roles Of Tsrnas In the Occurrence And Development Of Central...mentioning
confidence: 99%